Increasing Adolescent Awareness of Sexual and Reproductive Health Rights as an Effort to Prevent Early Marriage - Julietta Hutabarat; Elisabeth Surbakti; Efendi Sianturi; Maida Pardosi (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to increase adolescents' awareness of sexual and reproductive health rights to support the prevention of early marriage at SMA Negeri 1 Kutalimbaru, Deli Serdang Regency, Indonesia. The program employed a Participatory Action Research approach using a one-group pretest–posttest design involving 50 students. The intervention consisted of health education sessions, interactive discussions, presentation media, educational pocketbooks, posters, and the establishment of Youth Ambassadors as peer educators. Data on participants' knowledge, attitudes, and practices were collected through pretest and post-test questionnaires and analyzed descriptively using frequency and percentage distributions. The results demonstrated substantial improvements across all measured variables. The proportion of participants with good knowledge increased from 16% to 90%, positive attitudes from 18% to 96%, and good practices from 14% to 92%. Following the intervention, no participants remained in the poor category for any of the assessed variables. In addition, five Youth Ambassadors were established to promote the sustainability of peer-led reproductive health education within the school. These findings suggest that a structured and participatory reproductive health education program can effectively improve adolescents' knowledge, attitudes, and practices regarding early marriage prevention while fostering sustainable peer education initiatives.